Memória de formação: trajetórias e reflexões - CASTRO, Suely Pinheiro (2023)
The purpose of this memorial was to focus on my personal, professional and academic life to date, as well as describing my life course from elementary school to university through the collection of documents and photos of the periods. The same brings the beginning of my school life that was given from the 4 years of age in the then, preschool kindergarten preschool. Continuing with a trajectory full of difficulties and persistence related mainly to my first academic phase that occurred from 1st to 4th grade, now transformed into years of Elementary School. In this period beyond the lack of school materials, I was literate by traditional methods, common in the practices of teachers of the time. The interest in reconstituting my memory was first of all to obtain undergraduate degree in Pedagogy by, through a descriptive memorial. Also weighing the fact of not having any record made on my life, this will serve to put in the time the remarkable moments from childhood to the university. For the construction of this memorial was carried out a research of qualitative approach that has as method the life history or (biographical) method, where it is used as a methodology of education, seeks to investigate through the school life history, the importance and the challenges faced during the period of the school life, remembering those moments in which significant knowledge and experiences were acquired for my life is like going back to time and experiencing them again.